HIV gp120‐induced neuroinflammation potentiates NMDA receptors to overcome basal suppression of inhibitory synapses by p38 MAPK. Issue 4 (18th January 2019) - Zhang, Xinwen; Green, Matthew V.; Thayer, Stanley A.
Abstract: HIV‐associated neurocognitive disorder affects about half of HIV‐infected patients. HIV impairs neuronal function through indirect mechanisms mainly mediated by inflammatory cytokines and neurotoxic viral proteins, such as the envelope protein gp120. HIV gp120 elicits a neuroinflammatory response that potentiates NMDA receptor function and induces the loss of excitatory synapses. How gp120 influences neuronal inhibition remains unknown. In this study, we expressed a green fluorescent protein (GFP)‐tagged recombinant antibody‐like protein that binds to the post‐synaptic scaffolding protein gephyrin to label inhibitory synapses in living neurons. Treatment with 600 pM gp120 for 24 h increased the number of labeled inhibitory synapses. HIV gp120 evoked the release of interleukin‐1β (IL‐1β) from microglia to activate IL‐1 receptors on neurons. Subsequent activation of the tyrosine kinase Src and GluN2A‐containing NMDA receptors increased the number of inhibitory synapses via a process that required protein synthesis. In naïve cultures, inhibition of neuronal p38 mitogen‐activated protein kinase (p38 MAPK) increased the number of inhibitory synapses suggesting that p38 MAPK produces a basal suppression of inhibitory synapses that is overcome in the presence of gp120. Direct activation of a mutant form of p38 MAPK expressed in neurons mimicked basal suppression of inhibitory synapses. This study shows for the first time that gp120‐induced neuroinflammation increases the number of inhibitory synapses and that this increase overcomes a basal suppression of synaptic inhibition. Increased inhibition may be an adaptive mechanism enabling neurons to counteract excess excitatory input in order to maintain network homeostasis. Open Science Badges: This article has received a badge for *Open Materials* because it provided all relevant information to reproduce the study in the manuscript. The complete Open Science Disclosure form for this article can be found at the end of the article. More information about the Open Practices badges can be found athttps://cos.io/our-services/open-science-badges/ . Abstract : Synaptic changes underlie the neurocognitive impairments that often accompany HIV infection. We found that exposure to HIV envelope protein gp120 increases the number of inhibitory synapses between hippocampal neurons. Under basal conditions p38 MAPK suppresses the number of inhibitory synapses. HIV gp120 evokes the release of IL‐1β from microglia, potentiating GluN2A‐containing NMDARs and activating Src kinase. Src overcomes the p38 pathway to increase the number of inhibitory synapses. Neuroinflammation‐induced increases in inhibitory signaling may contribute to HIV‐associated neurocognitive disorder. Open Science: This manuscript was awarded with the Open Materials Badge. For more information see:https://cos.io/our-services/open-science-badges/